Presurgical Planning Using a Three-Dimensional Pulmonary Model of the Actual Anatomy of Patient with Primary Lung Cancer - Kanzaki, Masato; Kikkawa, Takuma; Shimizu, Toshihide; Maeda, Hideyuki; Wachi, Naoko; Isaka, Tamami; Murasugi, Masahide; Onuki, Takamasa (The Thoracic and Cardiovascular Surgeon, 2013)
Objectives Video-assisted thoracoscopic surgery (VATS) for both lobectomy and segmentectomy has been used widely for early stage nonsmall cell lung cancer (NSCLC). The objective of this study was to investigate the clinical feasibility of surgical planning using patient's actual three-dimensional (3D) pulmonary model for the thoracoscopic surgical treatment of early stage NSCLC.Methods We examined 57 patients with stage IA NSCLC ≤ 2 cm in diameter. Based on patient's actual 3D pulmonary model created by using a homemade software program called CTTRY (Tokyo Women's Medical University, Tokyo, Japan), both the location of and extent of tumor invasion were assessed, and a suitable type of VATS lung resection for an individual was selected.Results By the 3D models, tumors in 47 patients were localized within one segment, and other tumors (10 patients, 18%) were involved in multiple segments. VATS lung resections consisted of a single segmentectomy were performed in 25 patients; upper division resections, 9; lingulectomy, 5; extended segmentectomy, 7; single subsegmentectomy, 6; and multiple subsegmentectomy, 5. All 57 patients underwent successful VATS lung resection without massive bleeding.Conclusion Presurgical planning based on patient's actual 3D pulmonary model is useful for patients with stage IA NSCLC ≤ 2 cm in diameter and for selecting an appropriate VATS lung resection for an individual.
Keywords: surgical planning; three-dimensional; lung cancer; thoracoscopy; video-assisted thoracoscopic surgery; sublobar resection